Transformative Changes and Institutional Challenges towards Sustainability: The Case of an Indonesian Private University - Esti Dwi Rinawiyanti; Dianne Frisko Koan (Universitas Diponegoro, 2026)
The university is known as an agent of change, promoting sustainability to prepare future leaders with sustainability awareness. The demand for universities to offer solutions to sustainability issues is growing as universities' role in undertaking policies, programs, and actions towards sustainability becomes increasingly important. This study aims to explain the role of universities in developing countries, particularly private universities, in achieving sustainability. A case study approach is chosen to obtain more detailed information from the University of Surabaya, a private university in Indonesia. In-depth interviews, group discussions, observations, and document analysis have been undertaken to enrich the data. The study shows that private universities faced more complex considerations and challenges in achieving sustainable development. This study highlights that private universities tend to pursue their own sustainability strategies, primarily focused on securing financial funding and meeting mandatory regulatory requirements. According to this study, a sustainable university also needs top-level leadership commitment and an understanding of sustainability as an organizational culture.